A Convenient Route for the Synthesis of 3‐Deazaspongosine. Issue 1 (22nd November 2013) - Bande, Omprakash; Herdewijn, Piet
Abstract: The first chemical synthesis of the 3‐deazaspongosine nucleoside is described, starting from commercially available 4‐amino‐2, 6‐dichloropyridine. The key step is the introduction of required functional groups at the 2 and 6 positions of the 4‐amino‐3‐nitropyridine without any conflict in the synthesis of nucleobase. Regioselective nucleophilic substitution with allyl alkoxide at the 2 position of 4‐amino‐2, 6‐dimethoxypyridine, followed by sequential deallylation and chlorination led to the desired 2‐chloro derivative. Ring closure of the 3, 4‐diaminopyridine and stereoselective glycosylation of the imidazo[4, 5‐ c ]pyridine with tetraacetate‐protected ribofuranose gave only the N 9 ‐β‐isomer. A final nucleophilic displacement of the 6‐chloride by hydrazine followed by reduction with Raney Nickel gave the desired 3‐deazaspongosine. Abstract : The synthesis of 3‐deazaspongosine by the stereoselective glycosylation of imidazo[4, 5‐ c ]pyridine with tetraacetate‐protected ribofuranose is described. The key step is the synthesis of the nucleobase starting from 2, 6‐dimethoxy‐3‐nitropyridin‐4‐amine by introducing the required functional groups at the 2 and 6 positions through the regioselective addition of allyl alcohol.